2021
DOI: 10.1128/spectrum.00730-21
|View full text |Cite
|
Sign up to set email alerts
|

Akkermansia muciniphila Alleviates Dextran Sulfate Sodium (DSS)-Induced Acute Colitis by NLRP3 Activation

Abstract: The gut microbiota and host immune response interaction influences the progression of intestinal inflammatory disease. As a well-recognized next-generation probiotic, Akkermansia muciniphila has been proved to play a crucial role in the progression of colitis, but its underlying mechanism remains inconclusive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(102 citation statements)
references
References 47 publications
4
81
0
Order By: Relevance
“…After combing and analyzing the existing literature, we found that a large number of studies induced animal models of UC with 2.5% or higher concentration of DSS and carried out relevant basic studies on gut microbiome and immune inflammation. 36–39 Other studies have found that the relative abundance of some bacteria ( Bacteroides , norank_f_Muribaculaceae, Turicibacter , Romboutsia , Clostridium_sensu_stricto_1) in the intestinal tract of DSS-induced UC model changed significantly. 40–43 In addition, the altered bacteria could trigger changes in levels of relevant inflammatory factors.…”
Section: Introductionmentioning
confidence: 95%
“…After combing and analyzing the existing literature, we found that a large number of studies induced animal models of UC with 2.5% or higher concentration of DSS and carried out relevant basic studies on gut microbiome and immune inflammation. 36–39 Other studies have found that the relative abundance of some bacteria ( Bacteroides , norank_f_Muribaculaceae, Turicibacter , Romboutsia , Clostridium_sensu_stricto_1) in the intestinal tract of DSS-induced UC model changed significantly. 40–43 In addition, the altered bacteria could trigger changes in levels of relevant inflammatory factors.…”
Section: Introductionmentioning
confidence: 95%
“…It has been reported that antibiotic use during childhood alters the gut microbiota and increases susceptibility to IBD, suggesting an important role of gut microbiota in the maintenance of intestinal homeostasis ( 26 ). Several studies have found differences in the composition of the gut microbiota between healthy people and patients with IBD, with a remarkable reduction in A. muciniphila in patients with UC ( 16 , 27 ). Furthermore, it has been reported that A. muciniphila or Amuc_1100 (an outer membrane protein of A. muciniphila ) can attenuate DSS-induced colitis in mice.…”
Section: Role Of a Muciniphila In Protecting Again...mentioning
confidence: 99%
“…A recent study has shown that Amuc_2109, an enzyme secreted by A. muciniphila , also attenuated DSS-induced colitis in mice, increasing the expression of TJs and reducing the expression of the NLRP3 inflammasome ( 30 ). However, the protective effect of viable A. muciniphila against DSS-induced colitis was shown to be dependent of NLRP3 activation ( 27 ). Indeed, the role of NLRP3 in the regulation of intestinal homeostasis was previously elucidated, since NLRP3 -/- mice are more susceptible to the development of experimentally induced colitis ( 31 ).Additionally, it was demonstrated that the administration of A. muciniphila induced the proliferation of intestinal stem cells and boosted the differentiation of Paneth and goblet cells in the small intestine and colon of healthy mice or mice with gut damage caused by radiation and methotrexate.…”
Section: Role Of a Muciniphila In Protecting Again...mentioning
confidence: 99%
“…Intestinal dysbiosis exacerbates colitis by promoting ubiquitination and accumulation of the innate immune adaptor stimulator of interferon genes (STING) in myeloid cells [ 40 ]. Olu et al confirmed that oral administration of Akkermansia muciniphila strain BAA-835 considerably ameliorated colitis by modulating intestinal microecology [ 45 ]. Larsen et al reported that lysozyme leveraged gut microbiota to inhibit DSS-induced colitis [ 46 ].…”
Section: Discussionmentioning
confidence: 99%